Future burden of prostate cancer mortality in Brazil: a population-based study - Javier Jerez-Roig; Dyego L. B. Souza; Pablo F. M. Medeiros; Isabelle R. Barbosa; Maria P. Curado; Iris C. C. Costa; Kenio Costa Lima (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
Prostate cancer mortality projections at the nationwide and regional levels to the year 2025 are carried out in this ecological study that is based on an analysis of Brazilian trends between 1996 and 2010. The predictions were made for the period 2011-2025 utilizing the Nordpred program based on the period of 1996-2010, using the age-period-cohort model. A significant increase was observed in the Brazilian rates between 1996 and 2006, followed by a non-significant decrease. The projections indicate a decrease in rates at a national level as well as for the Central, South and Southeast regions. Increases are expected for the North and Northeast regions. In conclusion, a reduction in the mortality rates for prostate cancer in Brazil is expected to the year 2025, as well as for the Central, South and Southeast regions. However, an increase in the absolute number of deaths in all regions is expected due to the anticipated aging of the population.